Participatory constraint analysis regarding the adoption of IPM technologies in pointed gourd cultivation: An empirical study (Journal of the Bangladesh Agricultural University, 2010)
The empirical study revealed that among the various types of constraints (as perceived by the respondents) regarding the adoption of IPM technologies in the Pointed Gourd (Trichosan thes dioica Roxb.) production, the lack of knowledge of the respondents about the Economic Threshold Limit (ETL) concept ranked first closely followed by the lack of knowledge of the respondents regarding the bio-pesticides (under the category of knowledge and information constraints) in second position, the lack of knowledge of the respondents about the Integrated Pest Management (IPM) techniques ranked third position, closely followed by lack of training of the respondents on the proper use of pesticides in the fourth position. The result also showed that among six numbers of different categories of perceived constraints, knowledge and information constraints with a rank score of 2769 enjoyed first rank position, distantly followed by administrative and managerial constraints (with a rank score of 1586) in the second position, technological and communication constraints with a rank score of 1249 in the third position, socio-economic constraint (rank score of 828) in the fourth position. Keywords: Adoption of IPM techniques; Constraints; Categories of constraints DOI: 10.3329/jbau.v7i2.4722 J. Bangladesh Agril. Univ. 7(2): 219-227, 2009